Classical treatment of Li2++Ar and He2++Ar collisions. (July 2015) - Jorge, A; Illescas, Clara; Pons, B
Synopsis: Classical Trajectory Monte Carlo calculations are carried out for Li 2+ +Ar and He 2+ +Ar collisions, motivated by recent experiments on these systems. Cross sections for electron capture, projectile electron loss and target multiple ionization processes are evaluated and compared to the experimental values in the 75-500 keV/amy impact energy range.